Наші досягнення у вивчені причини та механізму розвитку вікового пародонтозу - Монастирський, В.А.; Гриновець, В.С. (Таврический медико-биологический вестник, 2012)
Установлено, что возрастной пародонтоз, как дегенеративно-дистрофическое повреждение
пародонта, является местным проявлением общего физиологического старения органима, в механизме
развития которого принимают участие два, осуществляемые тромбин-плазминовой системой,
процессы - биологической коагуляции (цито-гисто-гемокоагуляции) и биологической регенерации (цито-
гисто-геморегенерации). Непосредственной причиной старения организма (возрастного пародонтоза)
является генетически детерминировано преобладание в возрасте биокоагуляции над процессом
биорегенерации. Поскольку биокоагуляция функционирует как коагуляционно-гипотрофический
механизм, то это дало основания обосновать коагуляцино-гипотрофичны теорию развития
физиологического старения организма, а значит и возрастного пародонтоза. It was established that age-specific periodontosis, as degenerative-dystrophic periodontal damage is a
local manifestation of general physiological aging of the organism, in the development of which two processes
carried on by thrombin-plasmin system are involved: biological coagulation (cyto-histo-hemocoagulation) and
biological regeneration (cyto-histo-hemoregeneration). The direct cause of aging (age-specific periodontal
disease) is a genetically determined predominance of the process of biocoagulation over the process of
bioregeneration in older age. Since biocoagulation functions as a coagulation-hypotrophic mechanism, it gives
the reason to substantiate coagulation-hypotrophic theory of physiological aging, and thus age-specific
periodontosis. The above mentioned facts, allows to affirm that physiological aging, including age-specific
periodontal disease is actually a genetic-coagulation problem.